Healthcare Disparities among Socioeconomic Groups - Sharmake, Abdi (International Journal of Humanity and Social Sciences, 2024)
Purpose: This study sought to explore the socioeconomic factors contributing to disparities in healthcare access and outcomes. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to healthcare disparities among socioeconomic groups. Preliminary empirical review revealed that individuals from lower socioeconomic backgrounds faced multiple barriers to healthcare access, leading to inequalities in health outcomes. The study highlighted the complex interplay between social factors such as income, education, and wealth, emphasizing the need for comprehensive, multisectoral approaches to address healthcare disparities. Despite progress, gaps in research, policy, and practice remained, underscoring the importance of continued efforts to achieve health equity through collaborative initiatives and evidence-based interventions. Unique Contribution to Theory, Practice and Policy: The Social Determinants of Health theory, Health Benefit model and Critical Medical Anthropology theory may be used to anchor future studies on healthcare disparities among socioeconomic groups. The study provided comprehensive recommendations to advance theory, practice, and policy. It contributed to theoretical frameworks by highlighting the complex interplay between socioeconomic factors and healthcare disparities. In practice, it emphasized the importance of patient-centered care and collaborative models to address social determinants of health. Policy recommendations focused on structural interventions to improve social and economic conditions and expand healthcare coverage. Capacity building efforts aimed to enhance skills and competencies, while improved data collection and monitoring systems were advocated for tracking progress. Finally, a research agenda prioritized understanding the mechanisms underlying disparities and evaluating intervention effectiveness. These recommendations aimed to promote health equity and ensure equitable access to healthcare services.